Analysis of the Implementation of Regional Regulation No. 2 of 2024 of Central Kalimantan Province on the Recognition and Protection of the Dayak Customary Law Community in Dusun Selatan Subdistrict - Parunadi, Parunadi; Murhaini, Suriansyah; Sangalang, Rizki Setyobowo (Dinasti Research, 2025)
This study aims to analyze the implementation of the Provincial Regulation of Central Kalimantan Number 2 of 2024 concerning the Recognition and Protection of Indigenous Law Communities, particularly regarding the Dayak indigenous communities in Dusun Selatan District. The main focus of this regulation is to provide recognition and protection for the rights of indigenous communities, especially regarding land rights and indigenous culture, which have often been neglected in various development policies. This research uses a empiric juridical approach to assess how this regional regulation can protect these rights and identify the challenges in its implementation on the ground. The findings indicate that although Provincial Regulation Number 2 of 2024 provides a strong legal basis for the recognition of indigenous rights, its implementation still faces many challenges, especially in the legalization of indigenous land rights, outreach to indigenous communities, and the protection of indigenous cultures from the impacts of modernization and development. Therefore, while there are positive steps through this regulation, the protection of indigenous rights still requires more coordinated and effective efforts from all relevant parties to ensure these rights are fully realized